Sentinel Lymph Node Biopsy in Uterine Cervical Cancer Patients: Ready for Clinical Use? A Review of the Literature. (16th January 2014) - Palla, Viktoria-Varvara; Karaolanis, Georgios; Moris, Demetrios; Antsaklis, Aristides
Abstract : Sentinel lymph node biopsy has been widely studied in a number of cancer types. As far as cervical cancer is concerned, this technique has already been used, revealing both positive results and several issues to be solved. The debate on the role of sentinel lymph node biopsy in cervical cancer is still open although most of the studies have already revealed its superiority over complete lymphadenectomy and the best handling possible of the emerging practical problems. Further research should be made in order to standardize this method and include it in the clinical routine.